An Intersectoral Flows Analysis of the California Economy - Hansen, W. Lee; Tiebout, Charles M. (The Review of Economics and Statistics, 1963)
OUR empirical knowledge of the demand and structural interrelationships of the economy at the regional level is indeed limited. Some understanding of these interrelationships can be gained through (1) the economic baseforeign trade multiplier approach, (2) the regional interindustry (input-output) approach, and (3) various other approaches, involving linear programming and the like, which are not of concern here.' Although the interindustry approach seems superior to the base-multiplier approach for most, though not all, purposes, the real difficulty lies in translating either approach into an operational one so that meaningful estimates of these interrelationships can be generated at a reasonable cost. This is a rather unfortunate state of affairs because it means that decision makers have no firm guidelines to use in attempting to assess the impact of autonomous demand forces upon regional economies or specific sectors within them. In an attempt to at least partially remedy this situation, we have developed an alternative type of framework which, for the lack of a better name, can be called an intersectoral flows model. This model incorporates certain features of the base-multiplier approach in addition to certain features of a regional interindustry approach hopefully some of the best features of each in terms of our objectives. In designing the model, one of the main concerns was that it be operational, in the sense that the necessary data could be obtained at a reasonable cost. Thus, to the extent that this objective is achieved, the restrictions on making such studies and repeating them may no longer be so formidable. The particular region chosen for study is California and the three major subregions within the State. Since the interest here is in the model and its implementation, as contrasted with the implications for the California economy, major attention will be focused on these topics.